Пошаговое объяснение:
1-ая фотография
а) 3х-12=х
3х-х=12
2х=12
х=12/2
х=6
б) 4х-2=2х+6
4х-2х=6+2
2х=8
х=8/2
х=4
г) 2х+6=4х-2
2х-4х=-2-6
-2х=-8
2х=8
х=8/2
х=4
д) -4х-4=2х+8
-4х-2х=8+4
-6х=12
6х=-12
х=-12/6
х=-2
ё) 3х-2=6+4х
3х-4х=6+2
-х=8
х=-8
ж) 6х+6=4х-2
6х-4х=-2-6
2х=-8
х=-8/2
х=-4
и) 11+2х=55+3х
2х-3х=55-11
-х=44
х=44
й) -15-3х=-7х+45
-3х+7х=45+15
4х=60
х=60/4
х=15
л) 2(2+у)=19-3у
4+2у=19-3у
2у+3у=19-4
5у=15
у=15/5
у=3
м) (4-с)+2(с-3)=-13
4-с+2с-6=-13
-с+2с=-13-4+6
с=-11
2-ая фотография
в) -х=-9,1
х=9,1
г) -х+3=2
-х=2-3
-х=-1
х=1
д) -5+у=-4
у=-4-(-5)
у=1
ж) 4-t=0
t=4-0
t=4
з) -7-t=0
t=-7-0
t=-7
и) 2+5у=0
5у=0-2
5у=-2
у=-2/5
у=-0,4
к) 12а-1=-а+25
12а+а=25+1
13а=26
а=26/13
а=2
л) 8+3b=-7-2b
3b+2b=-7-8
5b=-15
b=-15/5
b=-3
н) 2-с=5с+1
-с-5с=1-2
-6с=-1
с=-1/-6
с=1/6
о) -3d-10=3d-6
-3d-3d=-6+10
-6d=4
d=4/-6
d=-4/6
3-ья фотография
а) 2х=9
х=9/2
х=4,5
б) -х=5,5
х=5,5
в) -х=-9,1
х=9,1
е) z-9=-3
z=-3+9
z=6
ё) t+5=0
t=0-5
t=-5
ж) 4-t=0
t=4-0
t=4
й) 9-4у=-5у
-4у+5у=-9
у=-9
к) 12а=1=-а+25
12а+а=25-12
13а=13
а=13/13
а=1
м) 4n+2=6n+7
4n-6n=7-2
-2n=5
n=5/-2
n=-2.5
н) 2-с=5с+1
-с-5с=1-2
-6с=-1
с=-1/-6
с=1/6
Пошаговое объяснение:
1-ая фотография
а) 3х-12=х
3х-х=12
2х=12
х=12/2
х=6
б) 4х-2=2х+6
4х-2х=6+2
2х=8
х=8/2
х=4
г) 2х+6=4х-2
2х-4х=-2-6
-2х=-8
2х=8
х=8/2
х=4
д) -4х-4=2х+8
-4х-2х=8+4
-6х=12
6х=-12
х=-12/6
х=-2
ё) 3х-2=6+4х
3х-4х=6+2
-х=8
х=-8
ж) 6х+6=4х-2
6х-4х=-2-6
2х=-8
х=-8/2
х=-4
и) 11+2х=55+3х
2х-3х=55-11
-х=44
х=44
й) -15-3х=-7х+45
-3х+7х=45+15
4х=60
х=60/4
х=15
л) 2(2+у)=19-3у
4+2у=19-3у
2у+3у=19-4
5у=15
у=15/5
у=3
м) (4-с)+2(с-3)=-13
4-с+2с-6=-13
-с+2с=-13-4+6
с=-11
2-ая фотография
в) -х=-9,1
х=9,1
г) -х+3=2
-х=2-3
-х=-1
х=1
д) -5+у=-4
у=-4-(-5)
у=1
ж) 4-t=0
t=4-0
t=4
з) -7-t=0
t=-7-0
t=-7
и) 2+5у=0
5у=0-2
5у=-2
у=-2/5
у=-0,4
к) 12а-1=-а+25
12а+а=25+1
13а=26
а=26/13
а=2
л) 8+3b=-7-2b
3b+2b=-7-8
5b=-15
b=-15/5
b=-3
н) 2-с=5с+1
-с-5с=1-2
-6с=-1
с=-1/-6
с=1/6
о) -3d-10=3d-6
-3d-3d=-6+10
-6d=4
d=4/-6
d=-4/6
3-ья фотография
а) 2х=9
х=9/2
х=4,5
б) -х=5,5
х=5,5
в) -х=-9,1
х=9,1
е) z-9=-3
z=-3+9
z=6
ё) t+5=0
t=0-5
t=-5
ж) 4-t=0
t=4-0
t=4
й) 9-4у=-5у
-4у+5у=-9
у=-9
к) 12а=1=-а+25
12а+а=25-12
13а=13
а=13/13
а=1
м) 4n+2=6n+7
4n-6n=7-2
-2n=5
n=5/-2
n=-2.5
н) 2-с=5с+1
-с-5с=1-2
-6с=-1
с=-1/-6
с=1/6
1) = (20 кг + 200г) * 6 = 120кг + 1200г = 120кг + 1кг 200г = 121кг 200г,
2) = 20,2 кг * 6 = 121,2 кг = 121кг 200г,
18т 9ц * 52 =
1) = (18т + 9ц) * 52 = 936т + 468ц = 936т + 46т 8ц = 982т 8ц,
2) = 18,9 т * 52 = 982,8 т = 982т 8ц,
11м 73см * 15 =
1) = (11м + 73см) * 15 = 165м + 1095см = 165м + 10м 95см = 175м 95 см,
2) = 11,73 м * 15 = 175,95 м = 175м 95 см,
82км 500м * 9 =
1) = (82км + 500м) * 9 = 738км + 4500м = 738км + 4км 500м = 742км 500м,
2) = 82,5 км * 9 = 742,5 км = 742км 500м,
6дм 7мм * 35 =
1) = (6дм + 7мм) * 35 = 210дм + 245мм = 210дм + 2дм 45мм = 212дм 45мм,
2) = 6,07 дм * 35 = 212,45 дм = 212дм 45мм